1989
DOI: 10.1021/j100338a035
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and electronic spectra of p-methoxybenzyl radical in the lowest excited doublet state in solution

Abstract: ROO• + R'SH -[ROOS(H)R'] -R'SO* + ROH (9) Reaction 9 is very similar in nature to reaction 8 and it is thus difficult to eliminate (9) as a competing mechanism. Further, the intermediate proposed is analogous to the intermediate [RSSS(H)R] suggested for the reaction of RSS* with RSH.37 Using bond energies of 170 kJ (0-0), 435 kJ (O-H), 380 kJ (S-H), and 360 kJ (S-O), we predict reaction 9 to be exothermic by approximately 245 kJ.38 Gilbert et al.31 found that sulfinyl radicals resulted from reaction of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
3
5
0
Order By: Relevance
“…The spectra exhibit a broad band at 510 nm, which is assigned to the p-methoxybenzyl radical and is similar to the band reported previously. 6 The fluorescence lifetimes, determined from photolysis of p-methoxytoluene and p-methoxybenzyl alcohol, are of a value of 141Ϯ12 ns and agree with the previous lifetime. 6 The fluorescence band disappears at a 100 s delay from the 266 to the 308 nm pulse.…”
Section: A Identification Of Radicalsupporting
confidence: 81%
See 3 more Smart Citations
“…The spectra exhibit a broad band at 510 nm, which is assigned to the p-methoxybenzyl radical and is similar to the band reported previously. 6 The fluorescence lifetimes, determined from photolysis of p-methoxytoluene and p-methoxybenzyl alcohol, are of a value of 141Ϯ12 ns and agree with the previous lifetime. 6 The fluorescence band disappears at a 100 s delay from the 266 to the 308 nm pulse.…”
Section: A Identification Of Radicalsupporting
confidence: 81%
“…6 The fluorescence lifetimes, determined from photolysis of p-methoxytoluene and p-methoxybenzyl alcohol, are of a value of 141Ϯ12 ns and agree with the previous lifetime. 6 The fluorescence band disappears at a 100 s delay from the 266 to the 308 nm pulse. The result shows that C-H bond fission in p-methoxytoluene and C-O bond scission in pmethoxybenzyl alcohol occur to form the p-methoxybenzyl radical.…”
Section: A Identification Of Radicalsupporting
confidence: 81%
See 2 more Smart Citations
“…[14][15][16][20][21][22] Tokumura et al observed the absorption spectra of p-methoxybenzyl and p-cyanobenzyl radicals in hexane solution at room temperature. 25,26 The absorption band is red-shifted relative to that of the p-cyanobenzyl radical. The origin band of m-methoxybenzyl radical was found to be surprisingly red-shifted.…”
Section: The Lif Excitation Spectrummentioning
confidence: 99%